Energy, exergy and environmental analysis of cold thermal energy storage (CTES) systems - Rismanchi, Behzad; Saidur, Rahman; Boroumandjazi, G.; Ahmed, Shamsuddin (Elsevier, 2012)
As the air conditioning system is one of the largest contributors to electrical peak demand, the role of the cold thermal energy storage (CTES) system has become more significant in the past decade. The present paper has reviewed the studies conducted on the energy and exergy analysis of CTES systems with a special focus on ice thermal and chilled water storage systems as the most common types of CTES. However, choosing a proper CTES technique is mainly dependent on localized parameters such as the ambient temperature profile, electricity rate structure, and user's habit, which makes it quite difficult and complicated as it depends on many individual parameters. Therefore, it was found that energy and exergy analysis can help significantly for a better judgment. The review paper has shown that the exergetic efficiency analysis can show a more realistic picture than energy efficiency analysis. In addition, the environmental impact and the economic feasibility of these systems are also investigated. It was found that, based on the total exergy efficiency, the ice on coil (internal melt) is known as the most desirable CTES system.